PERANCANGAN WEB PARIWISATA PADA DINAS KEBUDAYAN DAN PARIWISATA KABUPATEN PASAMAN BARAT DENGAN BAHASA PEMROGRAMAN PHP DAN DATABASE MYSQL - Masriadi Masriadi (Ensiklopedia of Journal, 2020)
In connection with the research conducted at the Culture and Tourism Office of West Pasaman Regency, particularly on the development and introduction of culture and tourism, several key points that need to be discussed and become a major concern in the process of developing and introducing culture and tourism are creating a website that contains culture and tourism. tourism that is packaged attractively so as to attract the interest of the community to visit West Pasaman Regency. This culture and tourism website is designed so that it can become a media of promotion and education so that it has a use value for the community. West.